Pengaruh Citra Merek (Brand Image), Pelayanan dan Religiusitas terhadap Keputusan Konsumen Membeli Produk Rabbani di Toko Nafasa Kedungwuni - Mustaghfiroh (2013112002) (Jurusan S-1 Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Pekalongan, 2017)
ABSTRACT Mustaghfiroh IAIN Pekalongan. 2017. The Influence of Brand Image (Brand Image), Religiosity and Service to Consumer Decision to Buy Prodak Rabbani at Nafasa Store Kedungwuni. Brand (brand) today developed into the largest and most valuable asset source for the company. Because a brand that is known to many people can make consumers glance at the product. A brand will create an image in the eyes of consumers, so the company must be able to determine the right marketing strategy that is one of Nafasa Store always try to give the best appearance, service and satisfaction to consumers in order to create a positive brand image in the eyes of consumers so it can influence consumer decisions In buying the product. Data collection method in this research is questionnaire method. Research subjects used as many as 96 respondents sempel, sampling technique with accidental sampling method. This type of research is field research. The data used are primary data and secondary data. This research is done by multiple linear regression test with the help of SPSS 16.0. The results of this study indicate that brand image variables affect the purchase decision with sig value 0.031 t table (2.188> 1.661). Service variables affect the purchase decision with sig value 0.031 t table (2.194> 1.661). Variable religiosity effect on purchasing decision with value sig 0.045 t table (2.035> 1.661). Then the value of adjust R on multiple regression analysis of 0.328, while the rest is explained by other independent variables which in this case did not become the author's research materials Keywords: Brand Image, Service, Religiusity and Purchase Decision